Patriarchal Culture in the Film "Marlina the Murderer in Four Acts" (Semiotic Analysis using John Fiske's Model) - Riris Angelina Nababan; Sofiari Ananda (International Journal of Business English and Communication, 2024)
structure, men hold the primary roles, while women have limited influence or even lack rights in various fields such as economics, social, political, and psychological, including the institution of marriage. This culture is particularly prevalent in certain communities. Patriarchal culture is often a subject of casual conversations, discussions, and even films, such as "Marlina The Murderer In Four Acts." This research analyzes patriarchal culture in the film using John Fiske's semiotic analysis. The coding can be divided into three levels: the level of reality, the level of representation, and the level of ideology. The findings of this research reveal numerous codes containing patriarchal culture, ranging from gestures, speech styles, environments, dressing styles, appearances, camera arrangements, actions, and lighting. The research also identifies the impacts of patriarchy in the film, such as subordination, marginalization, violence, stereotypes, and double burdens. The film portrays women's struggle against the patriarchal culture that still thrives in society.